Vertical Miscentering And Effect On Radiation Dose To The Lens In Computed Tomography Head Examination: A Systematic Review - Izdihar Kamal; Mohd Khairul Fazwan Mohd Yusof; Muhammad Khalis Abdul Karim; Nur Anis Izzati Che Mut; Suffian Mohamad Tajudin; Aminatul Saadiah Abdul Jamil (Elsevier, 2026)
Indexed by WOS / SCOPUS